Postdramatik: Dramaturgi Teater Indonesia Kontemporer - Afrizal Harun; Kurniasih Zaitun; Susandro Susandro (Institut Seni Indonesia Yogyakarta, 2021)
Postdramatic: The Dramaturgy of Contemporary Indonesian Theater. The research attempts to explain a new possibility in theatre practice in Indonesia, which was initially formed through the power of words in the form of dialogue depicted in drama scripts. Since then, there was another tendency which was a matter of fact, in the early 1920s, for which Antonin Artaud initiated. Various terms have been used to describe new trends in the dramaturgy of Indonesian theatre since the 1970s up to now, such as cutting-edge theatre, avant-garde theatre, experimental theatre, body theatre, visual/visual theatre, postmodern theatre, contemporary theatre, and so on. Therefore, the appearing terms show doubts in determining the identity of the currently developing Indonesian theatre. This study aims to explain the potential for postdramatic theatre works that have been performed by Indonesian theatre directors, such as WS Rendra, Putu Wijaya, Boedi S. Otong, Dindon WS, Rahman Sabur, Yudi A Tajudin, including Yusril with a Postdramatic theatre approach. This research method is dominated by literature studies that take references such as books, journal-based articles, and online and printed media. The results of the study indicate that postdramatic dramaturgy in the practice of theatre in Indonesia is necessary from the spirit of the times that formed it, including the possibility of creating a new form of post-dramatic theatre developing in the current era of the Covid-19 pandemic.Keywords: postdramatic; dramaturgy; theatre; Indonesia; contemporary